Use of corticosteroids in dental surgical procedures - Ferreira , Anderson Jara; Zevallos, Erick Andres Alpacas; Guimarães, Camila Coelho; Manrique, Gustavo Ramiro Rojas; Zanabria, Jaime S. Gallegos; de Santana, Ilan Hudson Gomes; Horikawa, Fernando Kendi; Shinohara, Élio Hitoshi (Brazilian Journal of Implantology and Health Sciences, 2025)
Background: Corticosteroids are widely employed in Oral and Maxillofacial Surgery (OMS) to mitigate postoperative inflammatory complications such as edema, pain, and trismus. Despite their extensive use, considerable variability remains regarding optimal protocols concerning dosage, route, and timing of administration. Objective: This narrative review aimed to critically evaluate the available scientific evidence on the efficacy, safety, and administration protocols of corticosteroids in OMS procedures. Methods: A descriptive exploratory narrative review was conducted. A comprehensive literature search was performed from May to June 2025 across PubMed/MEDLINE, Scopus, and Embase databases, using MeSH and DeCS terms alongside relevant free-text keywords. Studies included randomized trials, systematic reviews, meta-analyses, clinical guidelines, and cohort studies published between 2000 and 2025 in English, Portuguese, or Spanish. Data extraction focused on corticosteroid types, doses, routes, timing, clinical outcomes, and adverse events. Results: Evidence consistently demonstrated the clinical efficacy of corticosteroids—especially dexamethasone—in reducing postoperative edema, trismus, and pain, notably in third molar extractions, orthognathic surgeries, and facial fracture repairs. Intramuscular administration of 4–8 mg dexamethasone approximately 30–60 minutes preoperatively yielded the most significant benefits. Other corticosteroids such as betamethasone and methylprednisolone showed similar efficacy but different pharmacokinetics. Adverse effects were generally minimal with single short-term doses, though caution remains essential in patients with comorbidities. A lack of standardized protocols persists, underlining the need for individualized treatment plans. Conclusions: Corticosteroid use in OMS, when guided by well-established protocols and individualized patient assessment, is effective and safe for controlling inflammatory complications. Nevertheless, further high-quality randomized multicenter trials are warranted to establish robust standardized clinical guidelines.